Kritik Ulama’ Terhadap Pemikiran Bom Syahid Yusuf Qardhawi dalam Fiqh Al-Jihād Dirāsah Muqāranah Li-Aḥkāmihi Wa Falsafatihi Fi Dhau' Al-Qur'ān Wa Al-Sunnah - Ulfa Nur Fajriana; Dahliana, Yeti (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
The study aims to analyze Yusuf al-Qardhawi's thoughts on the martyrdom as stated in Fiqh al-Jihād's book: Dirāsah Muqāranah Li-Aḥkāmihi Wa Philosophy Fi Dhau' Qur'ān Wa Al-Sunnah, as aminah Li-Akāmihi Wa Philosophy. In Yusuf Qardhawi's view, martyrdom bombing was justified in the aspect of defensive jihad, especially in the Palestinian territories. However, Yusuf Qardhawi's views led to controversy and there were disagreements from a number of schools that argued that this was similar to Islam's outlawed suicide (al-intihar) and potentially led to innocent civil cases. This study uses a qualitative method of literature with primary sources, namely the book Fiqh al-Jihad Dirāsah Muqāranah Li-Aḥkāmihi Wa Falsafatihi Fi Dhau' Al-Qur'ān Wa Al-Sunnah and secondary sources in the form of Islamic literature in the form of research journals on disorders. This analysis uses descriptive analysis to fully explain Yusuf Qardhawi's position on the contents of the martyrdom bomb and compared to criticism from other schools, to find the boundary between the legitimate defense in Islam and the unwarranted acts of violence by Shariah.